The supply and control of money in the United States; together with A proposed revision of the monetary system of the United States, submitted to the Secretary of the Treasury, September 1934 - Currie, Lauchlin Bernard; Currie, Lauchlin Bernard; Brunner, Karl (New York : Russell & Russell, 1968)
This book examines the contributions of the monetary theory in US monetary mechanism, the reserve ratio and the effect of the banking structure on the money stock.
Includes index
Includes bibliographical references.
usc 09/04/18
Loans
Keywords: Money; Monetary policy; Federal Reserve banks; Banks and banking; Credit; United States